ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN WACANA PADA SISWA KELAS V SD NEGERI SE-GUGUS III KECAMATAN SAIL KOTA PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This research is caused by students less able to read the understanding of the discourse that is less interested students with reading activities, they just read but do not interpret the discourse that is read so they do not understand the content of the discourse, unable to conclude the discourse and determine the main sentence.This makes the student's ability to understand very low reading content. The formulation of this research problem is